VD_FINDINFO Décision / 2022 / 274 vom 28. März 2022 - VD Tribunal cantonal (2022)
DÉFENSE OBLIGATOIRE, PROCÈS-VERBAL, ADMINISTRATION DES PREUVES | 130 CPP (CH), 131 CPP (CH), 132 CPP (CH), 141 CPP (CH), 147 al. 1 CPP (CH)